A MULTIVARIATE ASSESSMENT OF VIDEO-CONFERENCING-MEDIATED INTERACTIONS: INVESTIGATING THE PREDICTORS OF STUDENT COMMUNICATIVE ADAPTATION (Contemporary Journal of Social Science Review, 2026)
The rapid shift toward online learning during the COVID-19 pandemic has increased reliance on video conferencing platforms such as Zoom and Microsoft Teams, raising important questions about their impact on students’ communication skills. While these platforms have enabled educational continuity, limited empirical evidence exists regarding their measurable effects on verbal and non-verbal communication competencies among university students in developing countries. The objective of this study was to examine how video conferencing platforms influence multiple dimensions of student communication, including verbal and non-verbal skills, engagement, confidence, collaboration, and perceived challenges. A quantitative, cross-sectional survey design was employed, and data were collected from 40 university students through a structured 47-item questionnaire using a 5-point Likert scale. Descriptive statistics and Pearson correlation analysis were conducted to examine relationships between platform usage variables and communication skill outcomes. The results indicated a mixed impact of video conferencing platforms on communication skills. Students reported high familiarity with these tools, along with significant challenges related to technical issues and internet connectivity. While confidence levels were relatively high, suggesting reduced communication anxiety, lower ratings were observed for engagement, communication skill development, and non-verbal communication. Correlation analysis revealed strong relationships among communication skills, engagement, confidence, collaboration, and overall satisfaction (r = 0.70 to 0.86), whereas challenges were only weakly related to these variables (r = -0.06 to 0.21). Overall, the findings suggest that video conferencing platforms provide both benefits and limitations. They support accessibility and psychological comfort but may hinder non-verbal communication and interaction quality. These results highlight the importance of effective teaching strategies and technological support in enhancing communication outcomes in virtual learning environments.